The Effect Of Heating Acrylic Resin Of Various Types With Different Temperatures On Impact Strength - didik marsigid; Handoko Tirta; Tasrip Tasrip (Politeknik Kesehatan Kemenkes Jakarta II, 2021)
Resin polymerization which is affected by unstable temperature causes the resin to break easily. The strength of the base material is affected by the forces acting in the mouth, such as transverse forces, other resistance or fatigue, and flexibility. Fracture of denture caused by masticatory loads and is affected by forces acting in the mouth, including transverse, resistance or fatigue, and flexural forces. Experimental Laboratory total of 72 samples consisting of 18 samples of type A, B and C cured at normal temperature, 100oC, 200oC, and 300oC. Types A, B and C have the effect of heating with the addition of temperature on the impact strength of acrylic resin, because the value of sig = 0.001 < 0.05, so H0 is rejected. An effect with the addition of temperature on the impact strength of the resin types A, B and C, because sig = 0.001 < 0.05, so H0 is rejected, which means that the average results are significantly different due to differences in temperature.